Open Functional Neck Dissection: Surgical Efficacy and Electrophysiologic Status of the Neck and Accessory Nerve - AKSOY, FADLULLAH; VEYSELLER, Bayram; ÖZTURAN, ORHAN; AKSOY, Fadlullah; YILDIRIM, YAVUZ SELİM; Ozturan, ORHAN; ACAR, Hurtan; ERTAS, Burak; BAYRAKTAR, Fatma Gulum Ivgin; SOYLU, Erkan; Yildirim, YAVUZ SELİM (My University, 2010)
Objective: To compare a novel functional neck dissection technique that offers wider exposure and reduced morbidity compared to classic functional neck dissection, which is the gold standard for neck treatment of squamous cell carcinoma of the head and neck.